EFL Teachers’ Professional Development: Towards a counterpart of the English Language Supremacy - Estacio, Aura María; Camargo Cely, Jennyfer Paola (GIST – Education and Learning Research Journal, 2018)
This article aims at contributing to the ongoing discussion about the English language Supremacy and its influence in the EFL field. The theoretical discussion presented is retrieved from the literature reviewed in the development of the authors’ master thesis, where it was possible to identify that there are ideological, economical, and sociopolitical aspects immersed in the decision to learn and use English, having as a result that EFL teachers’ educational decisions and practices have been affected. Thereupon, the main contribution of this reflection article is, then, to explore from a theoretical perspective, a resistance discourse that promotes professional development by understanding and reflecting upon the colonial ideas in which this foreign language teaching has been immersed over the years. Key words: English supremacy, colonial discourse, professional development, NES vs NNEST